2019
DOI: 10.1038/s41598-019-46839-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth regulators interact with elevated temperature to alter heat stress signaling via the Unfolded Protein Response in maize

Abstract: Plants are increasingly exposed to high temperatures, which can cause accumulation of unfolded protein in the endoplasmic reticulum (ER). This condition, known as ER stress, evokes the unfolded protein response (UPR), a cytoprotective signaling pathway. One important branch of the UPR is regulated by splicing of bZIP60 mRNA by the IRE1 stress sensor. There is increasing evidence that commercial plant growth regulators may protect against abiotic stressors including heat stress and drought, but there is very li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
(35 reference statements)
0
11
0
3
Order By: Relevance
“…ER stress elicits the unfolded protein response (UPR), a cytoprotective response to mitigate and to protect from this damage (Howell, 2013). The UPR is signaled through two pathways: one involving the proteolytic processing transcription factor bZIP28, and the other involving the ribonuclease IRE1, which mediates the splicing of the bZIP60 transcription factor mRNA (Neill et al, 2019). Both UPR pathways induce the expression of Heat Shock Proteins (HSPs) and activation of brassinosteroids (BRs) signaling (Che et al, 2010).…”
Section: Temperature Sensing and Signaling In Rootsmentioning
confidence: 99%
“…ER stress elicits the unfolded protein response (UPR), a cytoprotective response to mitigate and to protect from this damage (Howell, 2013). The UPR is signaled through two pathways: one involving the proteolytic processing transcription factor bZIP28, and the other involving the ribonuclease IRE1, which mediates the splicing of the bZIP60 transcription factor mRNA (Neill et al, 2019). Both UPR pathways induce the expression of Heat Shock Proteins (HSPs) and activation of brassinosteroids (BRs) signaling (Che et al, 2010).…”
Section: Temperature Sensing and Signaling In Rootsmentioning
confidence: 99%
“…One such intervention for alleviating waterlogging stress is supplementation with a plant growth regulator (PGR). PGR are often used to increase plant productivity, tolerance to stress, and self-repair qualitatively similar to the physiological and biological effects of phytohormones (Ali et al, 2015;Neill et al, 2019). Studies have demonstrated that PGRs can significantly increase the efficiency of the AsA-GSH cycle by removing the oxidative damage caused by the accumulation of ROS induced by environmental stress.…”
Section: Introductionmentioning
confidence: 99%
“…PhyB inactivation, which increases the abundance of phytochrome-interacting factors (PIFs), enhances heat stress tolerance by shifting the fatty acid composition from unsaturated to saturated forms ( Arico et al, 2019 ). In plants, high-temperature exposure leads to the accumulation of unfolded proteins in the ER, causing an ER stress response ( Neill et al, 2019 ). Phytochromes can integrate thermosensory signaling into the ER stress response.…”
Section: Discussionmentioning
confidence: 99%